2011
DOI: 10.1007/s12529-011-9181-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Working Memory Load on Performance and Cardiovascular Activity in Younger and Older Workers

Abstract: The data suggest that older workers as compared with younger ones are impaired in tasks requiring WM, which is accompanied by enhanced cardiovascular "costs" in terms of increased SBP and reduced vagal control over HR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 37 publications
5
25
3
1
Order By: Relevance
“…Several other studies have found an increase in SBP in response to cognitive performance in later adulthood (e.g., Boutcher & Stocker, 1996; Carroll et al, 2000; Hogan et al, 2012; Schapkin, Freude, Gajewski, Wild-Wall, & Falkenstein, 2012; Steptoe et al, 2005; Uchino et al, 1999). As noted earlier, a meta-analysis by Uchino et al (2010) also found that age differences in SBP reactivity increased with level of mean reactivity, suggesting that as task demands increase—as reflected in indices of active coping—so do age differences in SBP response.…”
Section: The Assessment Of Effortmentioning
confidence: 89%
“…Several other studies have found an increase in SBP in response to cognitive performance in later adulthood (e.g., Boutcher & Stocker, 1996; Carroll et al, 2000; Hogan et al, 2012; Schapkin, Freude, Gajewski, Wild-Wall, & Falkenstein, 2012; Steptoe et al, 2005; Uchino et al, 1999). As noted earlier, a meta-analysis by Uchino et al (2010) also found that age differences in SBP reactivity increased with level of mean reactivity, suggesting that as task demands increase—as reflected in indices of active coping—so do age differences in SBP response.…”
Section: The Assessment Of Effortmentioning
confidence: 89%
“…It is probably due to the fact that HR is regulated by both sympathetic and vagal pathways 13) which are highly susceptible to aging 14) . In a previous study we found that HR in the older group was more affected by sympathetic tone while in the younger group HR was associated with vagal influence 15) . Taken together, the results suggest that HR is only to a limited extent reliable to assess age effects on cardiovascular reactivity to WM load.…”
Section: Introductionmentioning
confidence: 80%
“…The systolic and diastolic blood pressure (SBP, DBP) reactivity to laboratory stressors is usually greater in older than in younger adults and is thought to be a marker of age-related sympathetic predominance that usually goes along with vagal withdrawal 5) . By contrast, younger people meet task demands by vagal withdrawal only while sympathetic tone (and hence SBP) remains constant during the experiment 15) . One of the most important mechanisms providing the maintenance of adequate BP in the cardiovascular system is the baroreflex 16) .…”
Section: Introductionmentioning
confidence: 91%
“…The process of natural aging is accompanied with a decrease in adaptive capacity, morphological and functional changes in major body's systems, that leads to cumulating decrease in general and occupational ability to work, mental and physical performance [26]. It causes limitations to perform certain occupational duties, or a significant increase in physiological cost of the work performed, and accordingly to disruption of adaptabilities and development of pathological conditions [29]. As a result, in the professions related to the need for rapid response, high coordination of movements, performing higher physical activities, the proportion of people in older age groups is lower.…”
mentioning
confidence: 99%